Integrasi Kearifan Lokal dalam Pembelajaran Sekolah Dasar di Indonesia: Systematic Literature Review - Tri Indah Sari; Eko Handoyo; Indriana Eko Armaidi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The integration of local wisdom into elementary school learning has garnered increasing attention alongside the implementation of the Merdeka Curriculum, which emphasizes contextual learning and the strengthening of the Pancasila Student Profile. This study aims to map the characteristics of existing research, synthesize key findings, and identify research gaps concerning the integration of local wisdom into elementary school learning in Indonesia during the period 2021–2025. A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 guidelines. Literature searches were performed using Google Scholar with keywords related to local wisdom, ethnopedagogy, ethnomathematics, ethnoscience, and elementary schools. Of the 347 articles initially identified, 20 met the inclusion criteria and were analyzed using a thematic synthesis approach. The findings reveal four main themes: (1) the use of traditional games and culture-based media contributes to psychomotor, cognitive, social-emotional, and numeracy literacy development; (2) local wisdom serves as a means of strengthening character education and the Pancasila Student Profile; (3) the application of ethnomathematics and ethnoscience supports conceptual understanding, mathematical communication, and critical thinking skills; and (4) research gaps persist, characterized by a scarcity of studies focusing on early elementary grades, limited representation from eastern Indonesia, and a lack of experimental and longitudinal research. Overall, the integration of local wisdom demonstrates significant potential as a contextual and meaningful learning strategy; however, its implementation still requires enhanced teacher capacity and the development of locally relevant instructional materials. These findings are expected to serve as a foundation for the development of instructional practices and more diverse, contextually grounded future research agendas.